Stress and Anxiety Scores in First and Repeat IVF Cycles: A Pilot Study - Turner, Kathy; Reynolds-May, Margaret F.; Zitek, Emily M.; Tisdale, Rebecca L.; Carlisle, Allison B.; Westphal, Lynn M. (PloS one, 2013)
The role of stress in reproduction, particularly during treatment for infertility, has been of considerable interest; however, few studies have objectively measured stress and anxiety over the course of the IVF cycle or compared the experience of first-time and repeat patients. This prospective cohort pilot study enrolled 44 women undergoing IVF at a university-based clinic to complete the State-Trait Anxiety Inventory (STAI), Perceived Stress Scale (PSS) and Infertility Self-Efficacy Scale (ISES) at three time points prior to ovarian stimulation (T1), one day prior to oocyte retrieval (T2), and 5-7 days post embryo transfer (T3). Mean STAI State scores were significantly elevated at all three time points (p<0.01). STAI State and PSS mean values did not change over time and did not differ in first-time vs. repeat patients. Self-efficacy (ISES) scores declined over time, with a greater decline for repeat patients. Of the 36 women who completed a cycle, 15 achieved clinical pregnancy. Using logistic regression modeling, all scores at T2 were correlated with pregnancy outcome with lower scores on the STAI State and PSS and higher scores on the ISES associated with higher pregnancy rates. Stress and anxiety levels remained elevated across all cycles. Women with lower stress and anxiety levels on the day prior to oocyte retrieval had a higher pregnancy rate. These results emphasize the need to investigate stress reduction modalities throughout the IVF cycle.